New insights into the biodiversity of coliphages in the intestine of poultry - Sørensen, P.E.; Broeck, W. van den; Kiil, K.; Jasinskyte, D.; Butaye, P.; Moodley, Arshnee; Garmyn, A.; Ingmer, H. (Springer, 2020)
Despite phages’ ubiquitous presence and great importance in shaping microbial communities, little is known about the diversity of specific phages in different ecological niches. Here, we isolated, sequenced, and characterized 38 Escherichia coli-infecting phages (coliphages) from poultry faeces to gain a better understanding of the coliphage diversity in the poultry intestine. All phages belonged to either the Siphoviridae or Myoviridae family and their genomes ranged between 44,324 and 173,384 bp, with a G+C content between 35.5 and 46.4%. Phylogenetic analysis was performed based on single “marker” genes; the terminase large subunit, portal protein, and exonucleases, as well as the full draft genomes. Single gene analysis resulted in six distinct clusters. Only minor differences were observed between the different phylogenetic analyses, including branch lengths and additional duplicate or triplicate subclustering. Cluster formation was according to genome size, G+C content and phage subfamily. Phylogenetic analysis based on the full genomes supported these clusters. Moreover, several of our Siphoviridae phages might represent a novel unclassified phage genus. This study allowed for identification of several novel coliphages and provides new insights to the coliphage diversity in the intestine of poultry. Great diversity was observed amongst the phages, while they were isolated from an otherwise similar ecosystem.